2019
DOI: 10.1002/ps.5312
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary food forNeoseiulus californicusboosts biological control ofTetranychus urticaeon strawberry

Abstract: BACKGROUND: A wide range of supplementary food resources can be offered to generalist predatory mites to improve their survival and reproduction and enhance their persistence in the environment. We investigated the relative suitability of different pollen types for the survival and reproduction of Neoseiulus californicus and its life history on a mixed diet of pollen and prey. We also evaluated the population dynamics of Tetranychus urticae in the presence of N. californicus with or without pollen, and in comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
10

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 60 publications
2
15
0
10
Order By: Relevance
“…Typha sp. was also found to be a high-quality diet in other studies (van Rijn and Tanigoshi 1999;Nomikou et al 2003;Messelink et al 2008;Goleva and Zebitz 2013;Lee and Zhang 2018;Ajila et al 2019). Performance of this strain Fig.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Typha sp. was also found to be a high-quality diet in other studies (van Rijn and Tanigoshi 1999;Nomikou et al 2003;Messelink et al 2008;Goleva and Zebitz 2013;Lee and Zhang 2018;Ajila et al 2019). Performance of this strain Fig.…”
Section: Discussionsupporting
confidence: 70%
“…The presence of alternative food can ensure the longer persistence of these organisms when food is scarce (Altieri and Letourneau 1982;Landis et al 2000;Duarte et al 2015;Gurr et al 2017). Several papers have shown the potential of pollen as alternative food for predatory mites (van Rijn and Tanigoshi 1999;Nomikou et al 2003;Goleva and Zebitz 2013;Montserrat et al 2013;Duarte et al 2015;Ajila et al 2019) and how it can be used to improve biocontrol (van Rijn et al 2002;Duso et al 2004;González-Fernández et al 2009;Nomikou et al 2010;Delisle et al 2015;Duarte et al 2015). However, only a few studies have investigated whether pollen quality can affect interactions between natural enemies and thus influence biological control.…”
Section: Discussionmentioning
confidence: 99%
“…They have different feeding habits allowing them to be classified as specialist (carnivorous) and generalist (omnivore), respectively . However, despite their different dietary habits, the two predatory species have been successfully used to control the two‐spotted spider mite Tetranychus urticae , a key strawberry pest …”
Section: Introductionmentioning
confidence: 99%
“…20,21 However, despite their different dietary habits, the two predatory species have been successfully used to control the two-spotted spider mite Tetranychus urticae, a key strawberry pest. [22][23][24][25][26][27] It has been shown that the lime sulfur causes a grater negative impact on the pest than on the natural enemies. 11,12,14,16,28 However, some studies observed concentration dependent adverse effects of lime sulfur on natural enemies of pest.…”
Section: Introductionmentioning
confidence: 99%
“…In mass production of natural enemies, selecting costeffective food sources is of critical importance in reducing cost in production. More recently, it was also suggested that provi sioning natural enemies with supplementary food improved the outcome of biocontrol through enhancing the survival and reproduction of predatory mites when prey is scarce or unavailable (Vacacela Ajila et al 2019). In this study, we determined the immature biology of N. cucumeris when they were offered a potential food source, T. curvipenis, a mite species from the same family of the factitious prey T. putrescentiae.…”
Section: Discussionmentioning
confidence: 99%